2015
DOI: 10.1016/j.jct.2015.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water concentration in the viscosities and densities of cellulose dissolving ionic liquids. Correlation of viscosity data

Abstract: a b s t r a c tThe densities and viscosities of aqueous mixtures of two cellulose dissolving ionic liquids: 1-allyl-3-methylimidazolium chloride and 1-ethyl-3-methyl imidazolium acetate ionic liquids have been experimentally determined for water concentration up to approx. 35% water at atmospheric pressure and temperature range from (298.15 to 373.15) K. Molar excess volumes were calculated, resulting in negative values. Literature viscosity correlations were modified in order to describe the viscosity as a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 25 publications
6
25
1
Order By: Relevance
“…Densities and viscosities of the pure ionic liquid as a function of temperature are listed in Table 1. In Figure 1 data were plotted together with literature data [ 20], [ 21], [ 22]. It is observed that both, density and viscosity decrease with increasing temperature and that the data determined in this work were consistent with literature data .…”
Section: Density and Viscosity Of The Pure Ionic Liquidsupporting
confidence: 83%
See 1 more Smart Citation
“…Densities and viscosities of the pure ionic liquid as a function of temperature are listed in Table 1. In Figure 1 data were plotted together with literature data [ 20], [ 21], [ 22]. It is observed that both, density and viscosity decrease with increasing temperature and that the data determined in this work were consistent with literature data .…”
Section: Density and Viscosity Of The Pure Ionic Liquidsupporting
confidence: 83%
“…It is observed that both, density and viscosity decrease with increasing temperature and that the data determined in this work were consistent with literature data . [ 20], [ 21], [ 22]…”
Section: Density and Viscosity Of The Pure Ionic Liquidmentioning
confidence: 99%
“…As an example, the viscosities of ILs/DESs can be decreased significantly by the addition of only a trace amount of water. 33 The mixing of water with ILs/DESs can be either endothermic, exothermic or both, depending on the water content. 34 In addition, the excess volume can be either positive, negative or both, thus generating an S-shaped curve.…”
Section: Chang Liumentioning
confidence: 99%
“…However, the deviation from the logarithmic mixing rule can still be quite significant. Jiménez de la Para et al [30] applied the Grunberg and Nissan [31] mixing rule for describing IL/water mixtures. This approach can be seen as a logarithmic mixing rule extended by correction terms.…”
Section: Introductionmentioning
confidence: 99%